2002
DOI: 10.1097/01.wcb.0000037993.34930.72
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Treatment with Tacrolimus (FK506) and Recombinant Tissue Plasminogen Activator for Thrombotic Focal Cerebral Ischemia in Rats: Increased Neuroprotective Efficacy and Extended Therapeutic Time Window

Abstract: The authors evaluated the therapeutic efficacy of tacrolimus (FK506), administered alone or in combination with recombinant tissue plasminogen activator (t-PA), on brain infarction following thrombotic middle cerebral artery (MCA) occlusion. Thrombotic occlusion of the MCA was induced by a photochemical reaction between rose bengal and green light in Sprague-Dawley rats, and the volume of ischemic brain damage was determined 24 hours later. Intravenous administration of tacrolimus or t-PA dose-dependently redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…In response to our request for further relevant information one author provided unpublished data. This meta-analysis is therefore based on data from 24 full papers published between 1994 and 2004 (Sharkey and Butcher, 1994;Sharkey et al, 1996;Kuroda and Siesjo, 1996;Butcher et al, 1997;Aoyama et al, 1997;Takamatsu et al, 1998Takamatsu et al, , 2001Yoshimoto and Siesjo, 1999;Kuroda et al, 1999;Toung et al, 1999;Bochelen et al, 1999;Miyazawa et al, 2000;Aronowski et al, 2000;Arii et al, 2001;McCarter et al, 2001;Ebisu et al, 2001;Fredduzzi et al, 2001;Maeda et al, 2002;Brecht et al, 2003;Furuichi et al, 2003a, b;Nito et al, 2004;Chung et al, 2004;Shichinohe et al, 2004), four abstracts Toung et al, 1997;Janelidze et al, 1999;McGregor et al, 2001) and one personal communication (J Aronowski); it represents the work of 14 independent groups, and nine of 29 publications came from groups funded directly by the Fujisawa Chemical Company, the manufacturers of FK506. Within the 29 studies, 109 comparisons (see Materials and methods for definition) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…In response to our request for further relevant information one author provided unpublished data. This meta-analysis is therefore based on data from 24 full papers published between 1994 and 2004 (Sharkey and Butcher, 1994;Sharkey et al, 1996;Kuroda and Siesjo, 1996;Butcher et al, 1997;Aoyama et al, 1997;Takamatsu et al, 1998Takamatsu et al, , 2001Yoshimoto and Siesjo, 1999;Kuroda et al, 1999;Toung et al, 1999;Bochelen et al, 1999;Miyazawa et al, 2000;Aronowski et al, 2000;Arii et al, 2001;McCarter et al, 2001;Ebisu et al, 2001;Fredduzzi et al, 2001;Maeda et al, 2002;Brecht et al, 2003;Furuichi et al, 2003a, b;Nito et al, 2004;Chung et al, 2004;Shichinohe et al, 2004), four abstracts Toung et al, 1997;Janelidze et al, 1999;McGregor et al, 2001) and one personal communication (J Aronowski); it represents the work of 14 independent groups, and nine of 29 publications came from groups funded directly by the Fujisawa Chemical Company, the manufacturers of FK506. Within the 29 studies, 109 comparisons (see Materials and methods for definition) were identified.…”
Section: Resultsmentioning
confidence: 99%
“…7) In addition to its immunosuppressive effects, tacrolimus has been reported to exert neuroprotective activity in a variety of animal models of cerebral ischemia. [8][9][10][11] The neuroprotective effect of tacrolimus has been explained by several mechanisms such as an anti-apoptotic effect via inhibition of cytochrome c release from mitochondria, an anti-inflammatory effect and so on. 12,13) However, the neuroprotective mechanism of tacrolimus has not been fully elucidated.…”
mentioning
confidence: 99%
“…Furthermore, the concentrations of tacrolimus in the blood and brain after administration of an effective dose at 0.1 mg/kg were comparable with those in rats given with effective doses of tacrolimus in focal ischemia models (Butcher et al, 1997;Furuichi et al, unpublished observations, 2002). Of interest, however, is the fact that the neuroprotective efficacy of tacrolimus in the present model ranks highly compared with other animal models (Furuichi et al, 2003;Maeda et al, 2002), with an 85% reduction of cortical infarction size at 24 hours and over a 50% reduction after 28 days. In addition to reducing infarct size, tacrolimus remarkably improved the motor system deficits and muscle coordination (Figs.…”
Section: Figmentioning
confidence: 92%
“…Previous studies have shown that tacrolimus has potent neuroprotective effects in a variety of rodent models of stroke, focal ischemia in rats (Bochelen et al, 1999;Butcher et al, 1997;Furuichi et al, 2003;Sharkey and Butcher, 1994), thrombotic focal ischemia in rats (Maeda et al, 2002;Takamatsu et al, 1998), and transient global ischemia in gerbils (Furuichi et al, 2003;Yagita et al, 1996). However, the predictive value of these models is limited given the numerous neuroprotectants that have failed in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation